EFFECTS OF A RESISTANCE TRAINING WITH ELASTIC TUBING IN STRENGTH, QUALITY OF LIFE AND DYPSNEA IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Silva, Bruna Spolador De Alencar; Gobbo, Luis Alberto; Freire, Ana Paula Coelho Figueira; Trevisan, Iara Buriola; Silva, Isis Grigoletto; Ramos, Ercy Mara Cipulo (Universidade Estadual de Maringá, 2016)
ABSTRACT The objective of this study was to analyze the effects of resistance training with elastic tubes and weight machines (conventional) on muscle strength, quality of life and dyspnea in patients with chronic obstructive pulmonary disease (COPD). Patients were allocated in training groups with elastic tubes (ETG, n = 9) and conventional (CRG, n = 10) and evaluated by isometric strength and quality of life questionnaire (CRQ) and dyspnea (MRC). Isometric strength increased by ~25% in both groups in all movements (p <0.05). MRC and the CRQ dyspnea domain showed improvement of -28.70% and -6.05% in the ETG, and -33.33% and -16.23% at CRG, respectively. Shoulder and elbow flexion showed a negative and significant correlation with MRC (p <0.05), for CRG. Both interventions were beneficial for increasing the strength and reducing the MRC score, and increased strength of upper limbs correlated to the reduction of the sensation of dyspnea in patients with COPD.

RESUMO O objetivo deste estudo foi analisar os efeitos do treinamento resistido com tubos elásticos e aparelhos de musculação (convencional) sobre a força muscular, qualidade de vida e dispneia em pacientes com doença pulmonar obstrutiva crônica (DPOC). Pacientes alocados em grupos de treinamento com tubos elásticos (ETG, n=9) e convencional (CRG, n=10) foram avaliados por força isométrica e questionários de qualidade de vida (CRQ) e dispneia (MRC). A força isométrica aumentou em ~25% em ambos os grupos em todos os movimentos (p<0,05). MRC e o domínio dispneia de CRQ apresentaram melhoras de -28,70% e -6,05 % no ETG, e -33,33% e -16,23% no CRG, respectivamente. Força de flexão de ombro e cotovelo apresentaram correlação negativa com a variável MRC (p<0,05) para CRG. Ambas intervenções foram benéficas para aumento da força e redução do MRC, com aumento da força de membros superiores correlacionado à redução da sensação de dispneia nos pacientes com DPOC.
EFEITOS DE UM TREINAMENTO RESISTIDO COM TUBOS ELÁSTICOS SOBRE A FORÇA MUSCULAR, QUALIDADE DE VIDA E DISPNEIA DE PACIENTES COM DOENÇA PULMONAR OBSTRUTIVA CRÔNICA
Keywords: Exercise; Chronic obstructive pulmonary disease; Quality of life; Exercício; Doença pulmonar obstrutiva crónica; Qualidade de vida